Probiotic, fructooligosaccharide and yeast extract mixture improves gut health in rainbow trout, Oncorhynchus mykiss - Ahani, Sara; Ahani, Saman; Taheri Mirghaed, Ali; Hoseini, Seyyed Morteza; Pagheh, Esmail; Arghideh, Mohammad; Yousefi, Morteza (Journal of animal physiology and animal nutrition, 2025)
The present study investigated the effects of a feed additive (FA) containing a probiotic consortium, fructooligosaccharide and yeast extract on growth performance, humoral immune responses, hepatic antioxidant parameters and intestine digestive enzymes, morphology and transcripts in rainbow trout, Oncorhynchus mykiss. The fish were reared for 8 weeks, feeding on diets containing 0 (CNT), 0.3 (0.3FA), 1 (1FA) and 2 (2FA) g/kg FA. The results showed that fish growth parameters were significantly and quadratically related to FA levels and FA treatments had better growth performance than CNT treatment. Intestinal amylase activity significantly increased in 2FA, whereas, intestinal protease activity increased in all FA treatments. Intestinal villus length and muscular layer thickness significantly increased in 0.3FA treatment. Blood leucocyte and lymphocyte counts, plasma lysozyme activity and hepatic glutathione content significantly increased in 0.3FA and 1FA treatments; whereas hepatic malondialdehyde significantly decreased in these treatments. Blood neutrophil and monocyte counts significantly increased in 0.3FA treatment, while plasma alternative complement activity significantly increased in 1FA treatments. Plasma bactericidal activities against Aeromonas hydrophila, Yersinia ruckeri and Streptococcus iniae, and intestinal expression of heat shock protein 70 and beta-defensin significantly increased in all FA treatments. The abundance of A. hydrophila, Y. ruckeri and S. iniae in fish gut significantly decreased in 0.3FA treatment; these bacteria were absent in the intestines of 1FA and 2FA treatments. The present results suggest that dietary 0.3-1 g/kg of FA can significantly improve growth performance, immune response, intestinal health and hepatic antioxidant capacity in rainbow trout.
Keywords: dieta; feed additive; kvasinky; Animal Nutritional Physiological Phenomena; Intestines; krmivo pro zvířata; potravní doplňky; probiotika; fructooligosaccharide; lactic acid bacteria; oligosacharidy; Probiotics; intestine; střeva; fyziologie výživy zvířat; Yeasts; zvířata; Dietary Supplements; Oligosaccharides; Animal Feed; blood; Diet; Oncorhynchus mykiss; Animals